Transformation of lamotrigine by white-rot fungus Pleurotus ostreatus. (July 2019) - Chefetz, Benny; Marom, Rotem; Salton, Orit; Oliferovsky, Mariana; Mordehay, Vered; Ben-Ari, Julius; Hadar, Yitzhak
Abstract: One of the most persistent pharmaceutical compounds commonly found in treated wastewater is lamotrigine (LTG). It has also been detected in soils and crops irrigated with treated wastewater. Here we focused on the ability of the white-rot edible mushroom Pleurotus ostreatus to remove and transform LTG in liquid cultures. At concentrations of environmental relevance (1 and 10 μg L −1 ) LTG was almost completely removed from the culture medium within 20 days. To elucidate the mechanism of LTG removal and transformation, we applied a physiological-based approach using inhibitors and a competing agent. These experiments were conducted at a higher concentration for metabolites detection. Based on identification of sulfur-containing metabolites and LTG N2-oxide and the effect of specific inhibitors, cytochrome P450 oxidation is suggested as one of the reaction mechanisms leading to LTG transformation. The variety and number of transformation products (i.e., conjugates) found in the current study were larger than reported in mammals. Moreover, known conjugates with glucuronide, glutathione, or cysteine/glycine, were not found in our system. Since the majority of the identified transformation products were conjugates of LTG, this study highlights the persistence of LTG as an organic pollutant in ecosystems exposed to wastewater. Graphical abstract: Image 1 Highlights: The white-rot fungus Pleurotus ostreatus removed lamotrigine from culture medium. Most identified metabolites were conjugation products. Carbamazepine addition decreases lamotrigine removal rate. Cytochrome P-450 is involved in lamotrigine metabolism.